2021
DOI: 10.5271/sjweh.4003
|View full text |Cite
|
Sign up to set email alerts
|

Associations of employment sector and occupational exposures with full and part-time sickness absence: random and fixed effects analyses on panel data

Abstract: Objective We aimed to investigate the influence of unobserved individual characteristics in explaining the effects of work-related factors on full (fSA) and part-time sickness absence (pSA). MethodsWe used register-based panel data for the period 2005-2016 on a 70% random sample of the Finnish working-age population. The relationships between employment sector and occupational exposures (% exposed to physically heavy work and job control score based on job exposure matrices) and the annual onset of fSA and pSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…However, among those with previous depression/anxiety, a higher proportion of young employees had long-term SA spells in the private as compared to the public sector. This finding adds an important aspect when discussing SA rates in public as compared to private sectors and especially among young employees 1 , 23 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, among those with previous depression/anxiety, a higher proportion of young employees had long-term SA spells in the private as compared to the public sector. This finding adds an important aspect when discussing SA rates in public as compared to private sectors and especially among young employees 1 , 23 .…”
Section: Discussionmentioning
confidence: 68%
“…Young employees with a history of depression/anxiety were shown to have approximately the same risk for future SA in both private and public sectors. However, several previous studies reported higher SA rates in public than private sector in different age groups, with one explanation being that the difference in SA rates may be attributable to employee’s health 1 , 2 , 7 , 23 . Our findings of young employees suggest that depression/anxiety in early years may explain the different SA rates in public and private sectors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The validity of the constructed JEM was tested by evaluating criterion-related validity using large population data. Based on solid evidence about possible links between psychosocial work exposures, especially high job strain (high job demand and low job control), and the risks of ill health, i.e., sickness absence (14), disability pension (15), and cardiovascular diseases (16) and different mental disorders (17; 18), such as risk for depressive symptoms (19,20) and sleeping problems (21,22), various health outcomes were taken into account to examine the reproducible likelihood of the constructed JEM compared with individual-based job exposure and the predictive validity of the JEM based on register data. The assessment of psychosocial work factors measured by JEM can also help to answer the question of whether the relationship between exposure and outcome is consistent regardless of the method used (16).…”
Section: Previous Researchmentioning
confidence: 99%
“…The validity of the constructed JEM was tested by evaluating criterion-related validity using large population data. Based on solid evidence about possible links between psychosocial work exposures, especially high job strain (high job demand and low job control), and the risks of ill health, i.e., sickness absence [ 14 ], disability pension [ 15 ], and cardiovascular diseases [ 16 ] and different mental disorders [ 17 , 18 ], such as risk for depressive symptoms [ 19 , 20 ] and sleeping problems [ 21 , 22 ], various health outcomes were taken into account to examine the reproducible likelihood of the constructed JEM compared with individual-based job exposure and the predictive validity of the JEM based on register data. The assessment of psychosocial work factors measured by JEM can also help to answer the question of whether the relationship between exposure and outcome is consistent regardless of the method used [ 16 ].…”
Section: Introductionmentioning
confidence: 99%